Prevalence of low backache in practicing dentists of Eastern region of Nepal - Shubham, S; Yadav, RP (Journal of Universal College of Medical Sciences, 2014)
AIM: To analyze the prevalence of low backache among practicing dentists of Eastern Region of Nepal. METHODS: A descriptive cross-sectional, questionnaire based study was conducted among the practicing dentists of Eastern region of Nepal from April 2012 July 2012. A pre-tested, pre-calibrated self-administered verbal rating questionnaire "The Oswestry Low Back Pain Disability Questionnaire" was distributed to a random sample of 85 dentists from different parts of eastern region of Nepal through direct contact and e-mails. RESULTS: A total of 85 dentists were identified among which 76 dentists participated in the research. Research finding showed that the prevalence of back pain among practicing dentists in Eastern region of Nepal was 90.79% among which 50% (minimal), 36.84% (moderate) and3.95% (severe). Among 45 males 4.44% had no back pain, 53.33% had minimal, 37.77% had moderate and 4.44% had severe back pain. On contrary females (31 participants) showed lesser prevalence of low back pain with 16.12% no back pain, 45.16% minimal, 35.48% moderate and3.22% severe back pain. The participants were divided into 3 different age group intervals in which dentists between 25-30 years were 50 in which 8% had no back pain, 58% had minimal, 28% moderate and 6% had severe back pain. Between 31-35 years were 22 participants in which 50% had minimal, 50% moderate and 0% had severe low back pain. More than 35 years were 4 participants in which 75% had no back pain, 25 % had moderate. Similarly the participants were divided into 5 different groups according the years of clinical practice in dentists having 1- 2 years of clinical practice (37 participants) had 2.70% no back pain, 56.75% minimal, 35.13% moderate and 5.40% severe back pain. 16 participants had 3-4 years of clinical practice out of which 12.50% had no low back pain, 62.50% had minimal, 18.75% had moderate and 6.25% had severe back pain. 10 participants had 5-6 years of clinical practice out of which 10% had no low back pain, 50% had minimal and 40% had moderate. 9 participants had 7-8 years of clinical practice out of which 11.11% had no low back pain, 33.33% had minimal and 55.55% had moderate. 5 participants had >9 years of clinical practice out of which 75% had no low back pain, 25% had minimal and 25% had moderate. CONCLUSION: The prevalence of back pain among dental personnel in Eastern region of Nepal was relatively high. The significant risk factors associated with it might be poor posture. Innovations for preventive and, ergonomic strategies should be undertaken to reduce the low back pain. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9570 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 29-32